(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The author trays to examine in this contribution the ways by wich the Palaeohispanic microtoponimy can be detected from the epigraphical documentation. The bronze of Fuentes de Ropel is an excellent example for this purpose.